Resource allocation: idealism, realism, pragmatism, openness. Issue 4 (December 1991) - Goodman, N W
Abstract : Lewis and Charny have come under siege for suggesting remote questioning to decide appropriate medical care. While the criticisms are theoretically valid, the idea is so important practically that Lewis and Charny should be supported and their approach investigated as a way of making medical treatment at least more open and possibly more fair.